Ground of logistic services’ activity effect’s calculation of interior troops units - Bondarenko О. H.; Vasilenko, V. P.; Kushneruk Yu. І.; Zozulya А. V. (Honor and Law, 2019)
The methodical approach of the logistic services’ activity effect’s calculation of Interior Troops units is given.